Ligand Engineering in Nickel Phthalocyanine to Boost the Electrocatalytic Reduction of CO2. (1st December 2021) - Chen, Kejun; Cao, Maoqi; Lin, Yiyang; Fu, Junwei; Liao, Hanxiao; Zhou, Yajiao; Li, Hongmei; Qiu, Xiaoqing; Hu, Junhua; Zheng, Xusheng; Shakouri, Mohsen; Xiao, Qunfeng; et al.
Abstract: Designing and synthesizing efficient molecular catalysts may unlock the great challenge of controlling the CO2 reduction reaction (CO2 RR) with molecular precision. Nickel phthalocyanine (NiPc) appears as a promising candidate for this task due to its adjustable Ni active‐site. However, the pristine NiPc suffers from poor activity and stability for CO2 RR owing to the poor CO2 adsorption and activation at the bare Ni site. Here, a ligand‐tuned strategy is developed to enhance the catalytic performance and unveil the ligand effect of NiPc on CO2 RR. Theoretical calculations and experimental results indicate that NiPc with electron‐donating substituents (hydroxyl or amino) can induce electronic localization at the Ni site which greatly enhances the CO2 adsorption and activation. Employing the optimal catalyst—an amino‐substituted NiPc—to convert CO2 into CO in a flow cell can achieve an ultrahigh activity and selectivity of 99.8% at current densities up to −400 mA cm −2 . This work offers a novel strategy to regulate the electronic structure of active sites by ligand design and discloses the ligand‐directed catalysis of the tailored NiPc for highly efficient CO2 RR. Abstract : A ligand‐tuned strategy is developed to boost the electrocatalytic reduction of CO2 and unlock the ligand‐directed molecular catalysis strategy. Nickel phthalocyanine decorated with electron‐donating substituents such as hydroxyl or amino can evoke electronic localization on the Ni site, enhancing the CO2 adsorption and activation. This promotes the catalytic reaction, which is positively associated with the electron‐donating abilities of substituents.